Correlation Between Usage of Academic Word List and Journal Rankings on English Studies in Indonesia - Mohamad Syafri; Najmi Hillaliyati; Nanik Shobikah; Mansur, Nurfauziah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
The development of scientific articles has dynamically improved, including in the English disciplines. Therefore, this study explores the relationship between using the Academic Word List (AWL) and the ranking of journals in English studies in Indonesia, with a particular focus on writing characteristics. Given the growing importance of academic vocabulary in language learning and the pivotal role of writing in academic success, this research aims to provide insights into how academic word usage correlates with journal quality. This study itself is quantitative research. 180 articles from 18 Sinta-accredited journals were analyzed using an electronic text analysis approach. The journals were chosen proportionally based on their Sinta’s rank. AntConc is used as the main application to analyze the lexical richness of the articles. The findings reveal that the overall lexical richness of the articles is 7.23%, with AWL words comprising 4.04% of the total vocabulary used. Despite these findings, statistical analysis indicates no significant correlation between the frequency of AWL usage and the journals' rankings. These results suggest that while AWL contributes to the lexical profile of academic writing, it does not directly influence journal ranking. Reasons could be assumed regarding these findings, such as journal’s editorial policies, authorial preference, and disciplinary variations. This study enhances our understanding of the elements of high-quality academic writing and offers valuable insights for teaching and learning academic writing. Teachers and lecturers of academic writing courses could explore and elaborate on AWL’s role in their teaching. Abstrak Perkembangan artikel ilmiah semakin dinamis, termasuk pada disiplin ilmu bahasa Inggris. Oleh karena itu, penelitian ini mengeksplorasi hubungan antara penggunaan Academic Word List (AWL) dan pemeringkatan jurnal dalam studi bahasa Inggris di Indonesia, dengan fokus khusus pada karakteristik penulisan. Mengingat semakin pentingnya kosakata akademis dalam pembelajaran bahasa dan peran penting menulis dalam keberhasilan akademis, penelitian ini bertujuan untuk memberikan wawasan tentang bagaimana penggunaan kata akademis berkorelasi dengan kualitas jurnal. Penelitian ini sendiri merupakan penelitian kuantitatif. 180 artikel dari 18 jurnal terakreditasi Sinta dianalisis menggunakan pendekatan electronic text analysis. Jurnal telah dipilih secara proporsional berdasarkan rangking Sinta. Dalam melakukan analisis terhadap lexical richness digunakan aplikasi AntConc. Temuannya mengungkapkan bahwa keseluruhan kekayaan leksikal artikel adalah 7,23%, dengan kata-kata AWL mencakup 4,04% dari total kosakata yang digunakan. Meskipun ada temuan ini, analisis statistik menunjukkan tidak ada korelasi yang signifikan antara frekuensi penggunaan AWL dan peringkat jurnal. Hasil ini menunjukkan bahwa meskipun AWL berkontribusi terhadap profil leksikal penulisan akademik, namun tidak secara langsung berhubungan dengan peringkat jurnal. Beberapa alasan yang diasumsikan menjadi dasar dari temuan, diantaranya kebijakan editorial dari jurnal, kecenderungan gaya menulis, dan ragam disiplim keilmuan. Studi ini meningkatkan pemahaman kita tentang unsur-unsur penulisan akademik berkualitas tinggi dan menawarkan wawasan berharga untuk pengajaran dan pembelajaran penulisan akademik. Para pengajar bagi kelas academic writing dapat secara lebih mengkaji dan mengelaborasi fungsi AWL dalam pembelajaran.Kata Kunci: academic word lis, ranking jurnal, kualitas menulis akademik, kekayaan leksikal